HEAT FLOW AND A GEOTHERMAL MODEL OF THE LITHOSPHERE BENEATH THE KOMANDORSKY BASIN, BERING SEA - Yanovskiy F.A.; Sugrobov V.M.; Seliverstov N.I. (My University, 1997)
Thermal structure of the crust beneath the Domandorsky Basin was modeled in the context of its tectonic evolution as a result of backarc rifting processes. The good fit of the theoretical heat flow to the results of heat flow measurements suggests that backarc spreading occurred in the central part of the basin from the Oligocene to the early Pliocene at an average half-rate of 1.5 cm/year, and that spreading continued in the west of the central sector from the early Pliocene to the Quaternary, inclusive. The heat flow anomalies observed in the southern Komandorsky Basin cannot be explained in terms of simple spreading models. The process of sea-floor grow there seems to have been caused by the development of several extension zones distributed along the strike of the southern sector, the zones where tectonic movements and magmatic activities occurred repeatedly.
Keywords: Pliocene; Oligocene; Quaternary; Cenozoic::Quaternary; Cenozoic::Neogene::Pliocene; Cenozoic::Paleogene::Oligocene; Кайнозой::Четвертичная; Кайнозой::Неоген::Плиоцен; Кайнозой::Палеоген::Олигоцен